ANIMASI FILM PENDEK “NOTHING CHANGE” - DESY CHAIRANI, Dini Faisal, S.Ds., M.Ds., Dra. Zubaidah, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The goal of this research is to create a short film animaton tittled “Nothing Change”. Short film animation“Nothing Change” is about a girl named clara, who is a dreamer but done nothing much to achieve it. What she had always done is waiting for the right moment and the right motivation to do something to achieving her dream. This story made for telling teenager these day to aware with their behavior in purpose to make their goal/dream comes true. Also, to change teenager perception about achieving their goal/dream.To design an impressive animation, designer collected data by done some research. Therefore, designer done some research by collecting data from literature study, interview, and direct observation. The data are use to develop a story and concept visual for animation. This short animation was made to give an inspiration to make a change.Keywords : Animation, Self-improvement, Short Film